Tinjauan Yuridis Penolakan Permohonan Kasasi oleh Mahkamah Agung Terkait Putusan Bebas dalam Tindak Pidana Korupsi - Enggelina Margaritha Fiah; Debi F.Ng. Fallo; Sigit Prabowo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Corruption and the rule of law are two things that are not foreign in the order of national, state and social life. Corruption seems to be a vocabulary that is experiencing inflation because it is most often used in almost all news reports. However, in corruption cases, judges are often less observant in paying attention to the facts presented in the trial so that often defendants in corruption cases are not punished commensurate with their actions, some even end in acquittals. The research method used by the author is normative legal research, by reviewing or examining laws and court decisions related to the legal problems faced. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials which are then analyzed descriptively qualitatively. The results of this study indicate that The basis for the Supreme Court's consideration in rejecting the public prosecutor's cassation application regarding the acquittal in corruption (Case Study of Supreme Court Decision Number: 2205 K/Pid.Sus/2022) is by considering the legal and non-legal aspects. Regarding the effectiveness of the decision in providing a deterrent effect for perpetrators of corruption in the future, judges in considering a decision should pay close attention to the facts in the trial so that the defendant's actions can be subject to sanctions and in the future can provide a deterrent effect on perpetrators of corruption in the future. The judge's consideration in imposing a sentence after the examination process in court must pay maximum attention to the sense of justice of the actions that have been committed by the defendant so that the verdict can provide a deterrent effect for perpetrators of corruption in the future.